Knowledge, Attitudes and Practices (KAP) regarding the Novel Coronavirus Disease (COVID-19) Post-lockdown in Trinidad and Tobago. Issue 5 (4th July 2021) - Selby, Lori; Tripathi, Vrijesh; Hariharan, Seetharaman
ABSTRACT: The Novel Coronavirus Disease (COVID-19) was declared a pandemic by the World Health Organization (WHO) in March 2020. Trinidad and Tobago reported its first infection on March 12 th 2020. This study assessed knowledge, attitudes and practices toward COVID-19 among Trinidadians during the post-lockdown period. A validated questionnaire was used to conduct a cross-sectional survey from May 25 th to June 6 th 2020. Most respondents (512, 96.6%) knew that COVID-19 is highly infectious. Many (523, 98.7%) identified vulnerable groups as persons 65 years and older and those with preexisting co-morbidities (480, 90.6%). Respondents identified COVID-19 symptoms as fever (498, 94.0%), dry cough (495, 93.4%), myalgia (403, 76.0%) and sore throat (441, 83.2%). Most 504 (95.1%) acknowledged that COVID-19 threatened the country's economy. Dominant practices included regular hand washing (97.2%) and social distancing (512, 96.6%). Health authorities should continue public education efforts to increase knowledge and the adoption of recommended practices.